The effects of xylene on distal convoluted tubules of Sprague dawley rats - Nur Farhana, Che Lah; Zul Izhar, Mohd Ismail; Nurul Aiman, Mohd Yusoff; Anani Aila, Mat Zin; Asma’, Hassan; Tg Fatimah Murniwati, Tengku Muda; Yasrul Izad, Abu Bakar; Lakshmi, Annamalai (2019)
The challenge that we will face in the next few years is the implementation of cost effective prevention and management strategies to avoid the xylene toxicity. Thus, investigations of xylene risk factors, toxicity and ways to reduce exposure to these factors are fundamentals. The purpose of this study was to investigate the toxicity effect of xylene on mean tubular diameter of distal convoluted tubules of kidney of female Sprague Dawley rats. Currently, the usage of xylene worldwide is increasing. Xylene is considered as a major industrial chemicals used in industrial field especially for products derived from petroleum refining. The important function of usage of xylene in industrial field is due to its ability as an intermediate chemical in producing many products including rubber, plastics, pesticides and leather. It is found in small amounts in airplane fuel, gasoline and cigarette smoke. Moreover, it is also widely used as a solvent in product such as inks, glues and paints. In histology laboratory staining procedures, its excellent dewaxing and clearing capabilities contribute to brilliantly stained slides.